Review of Ophthalmic Lens revolution / Nabila Mohd Norzri - Mohd Norzri, Nabila (2016)
Purpose: The purpose of this study has to explore the technology of the ophthalmic lens technologies available and their development and future. More specifically focusing on how to help optometry students to improve their knowledge of the ophthalmic lenses. Method: In selecting the research paper, there were several search engines being used. The search engines are Google Scholar, Wiley, Science Direct, SAGE, Scirus, Springer, Elsvier, Science-Hub, and PubMed. Besides, in compiling the development, the current and expected future of the ophthalmic products, more sources other than the articles or the journals only were required. The current products available information was obtained from the company websites and directly from the company themselves. Result: The traditional corrective lenses have been round and oval shaped. But moving through time, the lenses come in different shape, size, appearance and functions. The ophthalmic lenses now has not just being used for corrective purpose only, but had advanced to therapeutic purpose and much more. For example, the myopic control lens, a type of progressive lens that have a low addition portion to help children with the myopic power to focus their eyes to reduce stress and fatigue associated with the development and progression of nearsightedness. Conclusion: Ophthalmic lenses knowledge is important to every eye-care practitioner. Due to the lack knowledge between the practitioner, the compiled updated information and guidance is needed. In this study, there are some revolutions of ophthalmic lenses products and technologies were gathered. Besides, there were also tables of the current lenses available and the comparison between the functions, types, and the brands are constructed.